Effect of Cannabis sativa residue supplementation on meat quality, antioxidative capacity, and immune response in 34-day-old broiler chickens - Yusup Sopian; Katatikarn Sahatsanon; Apinya Satsook; Chaiwat Arjin; Chompunut Lumsangkul; Korawan Sringarm; Panneepa Sivapirunthep; Awis Qurni Sazili; Chanporn Chaosap (Italian Journal of Animal Science, 2025)
The overuse of antibiotics in animal feed has led to rising antibiotic resistance, highlighting the need for sustainable alternatives like herbal supplements. Cannabis sativa residues (CR), byproducts of the cannabis industry, have medicinal properties that may benefit poultry production. This study evaluated the effects of CR supplementation on meat quality, antioxidative capacity, and immune response in 34-day-old broiler chickens. A total of 256 male one-day-old Ross 308 chicks were randomly divided into four groups (0%, 0.5%, 1%, or 2% CR) and reared for 34 days. Broilers fed 1% CR had the highest eviscerated carcase yield, while those receiving 2% CR had the highest breast and intestine percentages (p < 0.05). A 2% CR dietary inclusion significantly elevated the pH of breast meat at 24 h post-mortem and reduced shear force and drip loss in breast meat (p < 0.05). Malondialdehyde levels in meat were significantly lower during storage (0, 3, and 5 days) in CR-fed groups (p < 0.01). No significant changes were observed in thawing loss, cooking loss, or meat colour (p > 0.05). While CR had no significant effect on immune-related gene expression, it significantly upregulated antioxidant-related genes such as catalase (CAT) and nuclear factor erythroid 2–related factor 2 (Nrf2) in the liver and increased Nrf2 expression in the jejunum (p < 0.05). Principal component analysis revealed positive correlations between CR supplementation and antioxidant gene expression. These results suggest that CR, at 0.5 to 2%, may enhance meat quality and antioxidant defense in broiler chickens.
Keywords: Animal Nutrition and Physiology; GABA and Rice Research; Biochemical effects in animals